Disparitas Gender dalam Pembangunan Antarwilayah di Jawa Timur: Studi Deskriptif Ekonomi Demografis dengan Pendekatan Gender-Related Development Index - Sri Kusreni; Achmad Syafii (EKO-REGIONAL, 2011)
The aims of this research are to identify gender disparity in interregional development in East Java Province and to get and present empirically the factors that cause the gender disparity in the research field; and to perceive the regions that dominate the contrast gender disparity. The research finds that the education attainment of male higher than female, exceptionally “Not yet completed Primary School” and “Primary school”. The regions which are belonged to this category are Banyuwangi, Situbondo, Bondowoso, Probolinggo (regency), Sumenep, Pamekasan, Sampang. Generally, labor participation rates of male and female in the municipality lower than that of in regency. This is caused since people (15-22 years old) tends to prefer going to school to working. Beside that, open unemployment in the municipality tends to be more higher than regency, both male and female. In terms of life expectancy, People of “Tapal Kuda” region has lower life expectancy than that of “Kulonan” region. Keywords: gender disparity, Gender-related Development Index